THE IMPACT OF DIVORCE OUTSIDE THE RELIGIOUS COURT ON THE SOCIAL LIFE OF THE COMMUNITIES IN ACEH UTARA AND ACEH BARAT - Zulfadli, Zulfadli; Aziz, Muchlis (JURNAL AL-IJTIMAIYYAH, 2024)
Divorce is a final path that must be taken in resolving household disputes and turmoil. If the cracks in the household can no longer be reconciled, it is feared that it will cause division between the two families. The objectives of this study are to understand the law of divorce in religious courts and outside of them, the factors causing divorce outside the religious courts, and to identify the impacts of divorce outside the religious court on the social life of the communities in Aceh Utara and Aceh Barat. This research uses a qualitative method, where the researcher thoroughly examines the facts found in the research locations according to the problem focus directly, then presents and discusses the analysis results. To obtain accurate and reliable data, data collection was carried out through observation, interviews, and documentation. The results show: (1) in Islamic law, divorce performed outside the religious court is valid, while the law of divorce outside the religious court is not valid under Indonesian law and the Marriage Law as well as the Compilation of Islamic Law; (2) the factors causing the community to divorce outside the religious court are due to adhering to the opinions of the Imam Mazhab and local ulama, due to customs, economic conditions, ignorance/lack of understanding of regulations, laziness in processing, and indifference to divorce laws; and (3) the impacts felt by the community after divorcing outside the religious court are not receiving the iddah rights, difficulty in remarrying. After all, they do not have a divorce certificate, as the KUA does not permit because they are still considered the wife of the first husband. Furthermore, they cannot claim joint property, hadhonah, and child support. This is consistent with what has happened to the people of Aceh Utara and Aceh Barat. Additionally, problems arising from divorce outside the religious court are related to children and their education, lack of legal certainty, asset distribution, inheritance, creating priority for the husband over the wife, the husband being arbitrary towards the wife, and child custody.